Pengaruh Rotasi Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PT. Kemuning Nusa Indah - Indah Handayani Safitri; Enjang Suherman (Jurnal Ekonomi dan Bisnis Digital, 2024)
This research aims to evaluate the impact of work rotation and work motivation on employee performance at PT. Kemuning Nusa Indah. The method applied is a descriptive method, using interview, observation and documentation techniques. The research results show that well-planned job rotation can increase employee adaptability, develop new skills, and reduce work burnout. In addition, high work motivation has a positive impact on employee performance, where motivated employees show greater commitment and contribution to the company. However, work rotation that is too frequent can cause discomfort and reduce employee motivation. In conclusion, job rotation and work motivation have a significant impact on employee performance, but need proper management to avoid negative impacts.